Nao-Xue-Shu Oral Liquid Protects and Improves Secondary Brain Insults of Hypertensive Cerebral Hemorrhage. (27th March 2016) - Jiang, Hongning; Qin, Ying; Liu, Te; Zhang, Liang; Wang, Mingzhe; Qin, Baofeng; Jiang, Wenfei; Liao, Weilong; Pan, Weidong
Abstract : Aim. To determine one traditional Chinese medicine (TCM) Nao-Xue-Shu oral liquid which protects and improves secondary brain insults (SBI) in hypertensive cerebral hemorrhage (HCH). Methods. 158 patients with HCH were divided into routine clinical medicine plus Nao-Xue-Shu oral liquid (n = 78 ) as treatment group, and routine clinical medicine (n = 80 ) only served as the control group. The incidence of SBI and the classification of a favorable prognosis and a bad prognosis using the Glasgow outcome scale (GOS) were assessed to evaluate the clinical effects. The changes of IL-6 and TNF- α levels were determined to study the mechanism of the effects for the TCM. Results. The incidence of SBI at the end of week 2 was 8.97% in the treatment group and 23.75% in the control group, and the difference was significant (P < 0.001 ). The incidence of a favorable prognosis was 48.72% in the treatment group and 32.72% in the control group, and the difference was significant (P < 0.01 ) at the end of week 2. These findings indicate clear differences for IL-6 and TNF- α at the end of week 1 and week 2 compared with before treatment for the treatment group and a marked difference at the end of week 2 between the two groups. It also shows a significant difference between the end of week 2 and before treatment for IL-6 and TNF- α for the control group, although the difference was much smaller than the treatment group. Conclusion. Nao-Xue-Shu oral liquid could protect against the occurrence of SBI and improve HCH and SBI patients. It may also decrease the damage and the mass effects of the hematoma by reducing IL-6 and TNF- α to obtain the effects, and thus it is a potentially suitable drug for HCH and SBI.